Variational structure and multiple solutions for a fractional advection–dispersion equation - Zhang, Xinguang; Liu, L.; Wu, Yong Hong (Elsevier, 2014)
By establishing a variational structure and using the critical point theory, we investigatethe existence of multiple solutions for a class of fractional advection–dispersion equationsarising from a symmetric transition of the mass flux. Several criteria for the existence ofmultiple nonzero solutions are established under certain assumptions.